Geometria do Táxi: uma introdução na Educação Básica - Oliveira, Mariana Mercílio de (2020)
This dissertation aims to present a didactic sequence on taxi geometry for the teacher who wants to work with this theme in the Basic Education classrooms. The didactic sequence consists of five activities that range from awake the student’s interest in the taxi distance to consolidating the concept of the taxi circumference, including the construction of the related formula to that distance and how to calculate the number of possible paths in this geometry. We also present the theoretical basis in which the taxi metric is inserted, serving as support material for the teacher.